Aliikangiella coralliicola sp. nov., a bacterium isolated from coral Porites lutea, and proposal of Pleioneaceae fam. nov. to accommodate Pleionea and Aliikangiella. Issue 11 (9th November 2020) - Wang, Guanghua; Dang, Ge; Xu, Shuailiang; Liu, Jianfeng; Su, Hongfei; Liang, Jiayuan; Huang, Wen; Wang, Yinghui; Yu, Kefu
Abstract : A novel Gram-stain-negative, non-endospore-forming, motile, and aerobic bacterial strain, M105 T, was isolated from coral Porites lutea, and was subjected to a polyphasic taxonomic study. Global alignment based on 16S rRNA gene sequences indicated that M105 T shares the highest sequence identity of 94.5 % with Aliikangiella marina GYP-15 T . The average nucleotide identity (ANI) and average amino acid identity (AAI) between M105 T and A. marina GYP-15 T was 69.8 and 71.6 %, respectively. On the basis of the results of phenotypic, chemotaxonomic, phylogenetic, phylogenomic, and comparative genomic analyses, it is concluded that M105 T should represent a novel species in the genus Aliikangiella, for which the name Aliikangiella coralliicola sp. nov. is proposed. The type strain is M105 T (=MCCC 1K03773 T = KCTC 72442 T ). Furthermore, the family Kangiellaceae was classified into two families on the basis of phylogenetic, phylogenomic, polar lipid profile and motility variations. The novel family Pleioneaceae fam. nov. is proposed to accommodate the genera Aliikangiella and Pleionea .